2013
DOI: 10.1242/jcs.134254
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Arf-GEF GBF1 to lipid droplets and Golgi membranes

Abstract: SummaryLipid droplet metabolism and secretory pathway trafficking both require activation of the Arf1 small G protein. The spatiotemporal regulation of Arf1 activation is mediated by guanine nucleotide exchange factors (GEFs) of the GBF and BIG families, but the mechanisms of their localization to multiple sites within cells are poorly understood. Here we show that GBF1 has a lipid-binding domain (HDS1) immediately downstream of the catalytic Sec7 domain, which mediates association with both lipid droplets and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 45 publications
3
85
1
1
Order By: Relevance
“…The HDS1 domain of human GBF1 bound directly to "Golgi-mix" liposomes and to artificial lipid droplets, and this interaction was inhibited in a construct comprising both the Sec7 and HDS1 domains. 40 Consistent with the inhibition of membranebinding elements in the HDS1 domain by the Sec7 domain, a yeast Sec7 construct encompassing the DCB-HUS-Sec7-HDS1 domains did not bind autonomously to membranes, yet it was about 5-fold more active on membranes than the shorter DCB-HUS-Sec7 construct. 41 These studies are consistent with a mechanism Table 1.…”
Section: Regulation Of Large Arfgefs By Direct and Small Gtpase-mediamentioning
confidence: 58%
See 2 more Smart Citations
“…The HDS1 domain of human GBF1 bound directly to "Golgi-mix" liposomes and to artificial lipid droplets, and this interaction was inhibited in a construct comprising both the Sec7 and HDS1 domains. 40 Consistent with the inhibition of membranebinding elements in the HDS1 domain by the Sec7 domain, a yeast Sec7 construct encompassing the DCB-HUS-Sec7-HDS1 domains did not bind autonomously to membranes, yet it was about 5-fold more active on membranes than the shorter DCB-HUS-Sec7 construct. 41 These studies are consistent with a mechanism Table 1.…”
Section: Regulation Of Large Arfgefs By Direct and Small Gtpase-mediamentioning
confidence: 58%
“…41 BIG1 and BIG2 (the mammalian orthologs of Sec7) also interacted with Arf-GTP in cells, but the region critical for interaction was mapped to the N-terminal DCB-HUS domains. 39 Interaction with Arf-GTP was not observed for yeast Gea1, which belongs to the other large ArfGEF subfamily 41 or for its human ortholog GBF1, 40 suggesting that it is specific to the Sec7/BIG subfamily. Other GTP-bound small GTPases have been reported to interact with large ArfGEFs and to regulate their localization and/or activities.…”
Section: Regulation Of Large Arfgefs By Direct and Small Gtpase-mediamentioning
confidence: 98%
See 1 more Smart Citation
“…The involvement of Trp residues in intracellular localization has been reported for a few lipid droplet proteins [32][33][34]. ALDH3B2 contains another Trp residue (Trp469), which is conserved in ALDH3B3, and which is located between Trp462 and the prenylation site ( Figure 5A).…”
Section: The C-terminal Regions Of Aldh3b2 and Aldh3b3 Determine Theimentioning
confidence: 71%
“…Biophysical analysis using NMR demonstrated that the aromaticity of Trp residues results in a tendency for these residues to reside in the electrostatically complex interface environment while the flat rigid shape of the Trp residue limits access to the hydrophobic moiety of the lipid chain [39]. Although the targeting mechanism of proteins to lipid droplets is largely unclear, the importance of Trp residues for lipid droplet localization has been previously reported for proteins including CGI-58, cholesteryl ester transfer protein, and the guanine nucleotide exchange factor GBF1 [32][33][34]. When the C-terminal region of ALDH3B2 was subjected to helical wheel plotting, the Trp462 and Trp469 residues and the prenylated Cys residue (Cys476) were closely oriented ( Figure 6C).…”
Section: Discussionmentioning
confidence: 99%